Management of petroleum hydrocarbon contaminated sites in Nigeria: Current challenges and future direction - Sam, Kabari; Coulon, Frederic; Prpich, George (Elsevier, 2017)
Sites affected by petroleum hydrocarbons from oil exploitation activities have been identified as a major environmental and socio-economic problem in the Niger Delta region of Nigeria. The current Nigerian regulatory instruments to manage these contaminated sites are fragmented and the roles and responsibilities of government agencies, such as the Department for Petroleum Resources (DPR), and the National Oil Spill Detection and Response Agency (NOSDRA), are not well defined. This lack of coordination has led to ineffective land contamination policy and poor enforcement more generally. Appropriate, risk-based policy instruments are needed to improve regulatory capacity, and to enhance the regulator's ability to manage new and existing petroleum hydrocarbons contaminated sites. Lessons can be learned from countries like the United Kingdom (UK) and the United States America (USA) that have experience with the management and clean up of historically contaminated land. In this paper, we review the status of petroleum hydrocarbon contaminated sites management in Nigeria and identify the gaps in existing policy and regulation. We review the contaminated land policies and regulation from the UK and the USA, and identify lessons that could be transferred to the Nigerian system. Finally, we provide a series of recommendations (e.g. source – pathway-receptor approach, soil screening criteria, clean-up funding, liability) that could enhance contaminated land legislation in Nigeria.
Keywords: Contaminated-land; Risk management; Niger Delta; Environmental policy; Oil spill